Konversi Akad dan Penerapannya dalam Perspektif Fiqih dan Hukum Legal - Ahmad Faisal; Trisiladi Supriyanto; Hari Susanto (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
Long economic recession caused by pandemi covid-19 impacts strongly to the quality of credit’s payment because customer’s payment ability is weaken. In order to solve non performing financing, the government of Indonesia announced the implementation of restructuritation to recover economic condition according to rule from Bank of Indonesia (BI) and Financial Services Authority (OJK). The purpose of this research is to study one of instrument for financing restructuritation namely contract conversion from fiqih’s perspective and legal law’s perspective in concept and implementation. The type of this research is library research with qualitative approach and using descriptive-comparative analysis. Based on this research is found that contract conversion as an instrument was explained detailly in legal rule of restructuritation. The concept of contract conversion was explained in fiqih muamalah with variative implementation. Legal law in economy from some moslem’s country talks about the concept of contract conversion and the way of implementation. In Indonesia, the guidance of legal law is rule of BI and rule of OJK as state institutions who have authority to rule banking and financial system. The implementation of contract conversion in Shariah Bank is also referred to edict of DSN-MUI. The results are 1) Contract conversion is transformation from non performing financing which has ran by stopping it and then create a new contract in different form without new subject, 2) Contract conversion in fiqih’s perspective is more extensive than legal law’s perspective, but legal law is more detailed in technical of implementation. Keywords: contract conversion, fiqih, legal law, Shariah Bank/Islamic Bank